FAULT PATTERN IN CONTINENTAL ZONES OF LITHOSPHERIC EXTENSION - Seminsky K.Zh. (My University, 2004)
A typical pattern shared by second-order faults in extended lithosphere was revealed based on field geological and structural data from the Obruchev Fault in the Baikal Rift and published evidence of rift-related faulting worldwide. The typical fault family is dominated by rift-parallel synthetic and antithetic normal faults and includes transverse faults of normal, strike-slip, and oblique slip geometry and rift-parallel reverse faults and thrusts. The coexistence of faults of various types within first-order extension zones is accounted for by accommodation of shear strain and by the kinematics of large basin-parallel normal faults. The suggested typical pattern can be used for reference in interpretation of faulting histories in rifted continental lithosphere.
Keywords: Faults; faulting pattern; Baikal rift; zones of extension